Strategies Deployed by Educators for Vocabulary Enrichment - Moh. Choirul Huda (STKIP PGRI Tulungagung, 2023)
The teaching and learning of English in non-English speaking countries always sparks public discussions. Having a sufficient vocabulary is crucial for effectively using a foreign language; without a broad range of words, it becomes difficult to employ the language structures and functions learned for meaningful communication. As a result, teachers need to be creative in applying vocabulary teaching strategies during the process of teaching and learning English as a foreign language (EFL). With this background in mind, the writer conducted research to investigate the strategies employed by English teachers at SDI Zumrotus Salamah Tulungagung. This particular school encourages active use of English in day-to-day activities. The research followed a qualitative design, involving 3 teachers from SDI Zumrotus Salamah as participants. Purposive sampling was used to focus on individuals and features most relevant to the study's objectives. Data collection methods included observation and interviews. The findings revealed that the teachers effectively utilized strategies such as the Determination Strategy, Social Strategy, Memory Strategy, Cognitive Strategy, and Metacognitive Strategy to cater to the learners' vocabulary needs. The study's results are expected to provide valuable insights for teachers, educators, and future researchers on the subject of teaching English vocabulary.